Determinants of Total Factor Productivity (TFP) among Sugarcane Farmers in Kwara State of Nigeria - S, Sadiq, M.; I.P., Singh; M.M, Ahmad,; M, Lawal (Jordan Journal of Agricultural Sciences, 2022)
The present research empirically determined the factors influencing total factor productivity (TFP) of sugarcane producers in the Kwara State of Nigeria. Data were obtained from using the 2017-2018 sugarcane cropping season field survey through the administration of a structured questionnaire complemented with an interview schedule on 105 sugarcane farmers selected via multi-stage sampling technique. The collected data were analyzed using the conventional TFP index and censored regression model. From the empirical findings, it was observed that inefficiency in the allocation of working capitals, capital consumption, and health-related challenges decreased the TFP of sugarcane farmers in the studied area. However, the study advised the extension agents to educate farmers to be rational in resource allocation in order to optimize their productivity in sugarcane production. In addition, the study advised farmers to adopt health precautious measures in order not to predispose their family members to tropical diseases and should imbibe savings and investment cultures